Hydrate‐filled Fracture Formation at Keathley Canyon 151, Gulf of Mexico, and Implications for Non‐vent Sites. (6th November 2019) - Oti, Emma A.; Cook, Ann E.; Welch, Susan A.; Sheets, Julia M.; Crandall, Dustin; Rose, Kelly; Daigle, Hugh
Abstract: Near‐vertical hydrate‐filled fractures are found in subseafloor marine muds, at both advective methane vent sites and at sites without obvious methane and fluid advection (non‐vent sites). At non‐vent sites, the mechanisms that transport methane to the fractures and control how hydrate‐filled fractures form are not well understood. However, these mechanisms are important to establish, as most of Earth's natural gas hydrate is likely bound in marine mud systems. Herein, we focus on understanding the origin of hydrate and how fracture form at non‐vent sites by examining previously hydrate‐bearing fractures in conventional cores taken from Keathley Canyon 151, U.S. northern Gulf of Mexico, drilled by the Gas Hydrate Joint Industry Project in 2005. We combine information from well logs, sediment cores, and science party results and add new X‐ray computed tomography of archival sections and scanning electron microcopy of core samples to develop a conceptual model. We propose that locally generated microbial methane is transported via diffusion from small pores in marine mud into biomineralized burrows with larger pore size in a process called short‐range migration. Hydrate forms in burrows once the methane diffuses into them and the dissolved methane concentration exceeds the solubility threshold. When hydrate fills a burrow, heave from additional hydrate growth places stress on the burrow edges, expands the fracture, and creates additional void space in which methane can diffuse and continue forming hydrate. Fractures slowly propagate in the direction of maximum principal stress. Plain Language Summary: Gas hydrates are formed when methane and water molecules combine at high pressures and low temperatures to create an ice‐like solid. They are found in a wide variety of marine and permafrost environments and can occupy fractures in subseafloor marine sediment. Often, fractures are caused by gas venting from sources below the seafloor. However, hydrate‐filled fractures are also observed in areas without gas vents and thus without connection to an obvious gas source. This paper presents a possible mechanism for hydrate fracture formation at non‐vent sites by analyzing marine sediment samples from a nonvent site in the northern Gulf of Mexico. Our results indicate methane here was formed by sediment dwelling bacteria and that this methane filled partially fossilized burrow tubes left by small marine organisms. Once methane concentrated in burrows tubes, gas hydrate began to form, and additional gas hydrate growth expanded burrows and generated fractures in the sediment. It is important to understand the hydrate systems at such sites form, because hydrate is an important part of the carbon cycle, and these systems likely contain most of the Earth's supply. Key Points: We propose a mechanism for hydrate‐filled fracture formation from methane generated in marine muds Locally generated methane diffuses from marine muds to sites with larger pore spaces that are more suitable for hydrate nucleation Bioturbation burrows, vugs, or isolated coarse‐grained sediments are optimal sites for hydrate‐fracture nucleation